2021
DOI: 10.3389/fendo.2021.734432
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Radiofrequency Ablation Versus Surgical Resection for the Treatment of T1bN0M0 Papillary Thyroid Carcinoma in Different Age Groups

Abstract: PurposeWe aimed to compare the efficacy and safety of radiofrequency ablation (RFA) to that of surgical resection (SR) in patients with T1bN0M0 papillary thyroid carcinoma (PTC) in different age groups.MethodsTotally, 204 patients with an isolated, solitary, intrathyroidal T1bN0M0 PTC, who underwent either RFA (n=94) or SR (n=110) between April 2014 and December 2019, were retrospectively enrolled and were divided into two subgroups according to age (<45 years, ≧45 years). Patients with pathologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…During a mean follow-up of 22 months, the nodule disappearance rate, the disease progression, and the complication rates were higher in the T1b group than in the T1a group; however, thermal ablation showed effectiveness and safety for T1N0M0 PTC. Studies comparing the efficacy and safety of RFA treatment and surgical resection in patients with T1bN0M0 PTC belonging to different age groups (59) showed that RFA was more cost effective and associated with a shorter operative time than the surgical group, but there was no significant difference in tumor progression and complication rates. In addition, subgroup analyses of patients older than fortyfive years and patients younger than forty-five years showed no significant differences in the incidence of tumor progression and complications.…”
Section: Ablation Of Ptc (Nodule Diameter >1 Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…During a mean follow-up of 22 months, the nodule disappearance rate, the disease progression, and the complication rates were higher in the T1b group than in the T1a group; however, thermal ablation showed effectiveness and safety for T1N0M0 PTC. Studies comparing the efficacy and safety of RFA treatment and surgical resection in patients with T1bN0M0 PTC belonging to different age groups (59) showed that RFA was more cost effective and associated with a shorter operative time than the surgical group, but there was no significant difference in tumor progression and complication rates. In addition, subgroup analyses of patients older than fortyfive years and patients younger than forty-five years showed no significant differences in the incidence of tumor progression and complications.…”
Section: Ablation Of Ptc (Nodule Diameter >1 Cm)mentioning
confidence: 99%
“…In contrast, ablation techniques commonly use local infiltration anesthesia, which is associated with fewer complications and is safer. A comparison of the efficacy and safety of RFA and surgical resection in patients with T1bN0M0 PTC >45 years of age (59) showed that the prognosis was similar in both groups; however, the overall cost and complications were lower in the ablation group, indicating that RFA may be an effective and safe alternative to surgery for the treatment of patients with T1bN0M0 PTC. The effect of age on the results of thermal ablation needs to be validated over a longer period of time and in larger studies.…”
Section: Agementioning
confidence: 99%
“…A total of six studies were identified (34)(35)(36)(37)(38)(39). Details of these studies are shown in Tables 1, 2.…”
Section: Identified Studiesmentioning
confidence: 99%
“…It is noteworthy that, thermal ablation may not be inferior to surgery oncologically, and it is a relatively safe and cost-effective treatment option for PTMC and single T1N0M0 stage PTC. Seven retrospective studies with a total of 867 patients were included in a systematic review and meta-analysis ( 79 ). Thermal ablation was found to reduce complication with a pooled odd ratio of 0.24(95% CI 0.13 to 0.43), postoperative length of stay with a pooled standardized mean difference of -3.14(95% CI -4.77 to -1.51), and cost during the perioperative period with a pooled standardized mean difference of -1.69(95% CI -3.18 to -0.20), according to the study ( 79 ).…”
Section: Progress and Challenges In The Clinical Applications Of Ultrasound-guided Thermal Ablation In Malignant Thyroid Nodulesmentioning
confidence: 99%
“…Seven retrospective studies with a total of 867 patients were included in a systematic review and meta-analysis ( 79 ). Thermal ablation was found to reduce complication with a pooled odd ratio of 0.24(95% CI 0.13 to 0.43), postoperative length of stay with a pooled standardized mean difference of -3.14(95% CI -4.77 to -1.51), and cost during the perioperative period with a pooled standardized mean difference of -1.69(95% CI -3.18 to -0.20), according to the study ( 79 ). Also, researchers compared the efficacy and safety of RFA to surgery in patients with T1bN0M0 PTC of various ages.…”
Section: Progress and Challenges In The Clinical Applications Of Ultrasound-guided Thermal Ablation In Malignant Thyroid Nodulesmentioning
confidence: 99%